Spolupráce elektrárenských bloků - optimalizace provozních parametrů - Hromádka, Martin (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2016)
Práce má za cíl popsat princip fungování tepelné kondenzační elektrárny, popsat problematiku týkající se zvyšování účinnosti výrobních bloků a sestavit matematický model paralelně spolupracujících bloků. V práci je rovněž vysvětlena základní problematika rozvodu elektrické energie a fungování elektrizační soustavy České republiky. V práci jsou provedeny výpočty dvou paralelně spolupracujících bloků pro případ kdy optimalizované výkony nevybočují z regulačních rozsahů, ale také pro případ, kdy vybočují. Jako součást práce byl zhotoven matematický model, který na základě zadaného výkonového požadavku v síti optimalizuje výkony mezi tři paralelně spolupracující bloky tak, aby byly celkové náklady na provoz co nejmenší. V modelu je rovněž možno provést kompletní výpočet měrných spotřeb a tepelných účinností na základě libovolně zadaných parametrů, a to pro pět různě technologický vybavených bloků.

This bachelor’s thesis aims to describe the principle of operation of thermal power plant as well as to describe the issues related to increasing the efficiency of production units. Another task was to create a mathematical model of cooperation of power plant units. The thesis also deals with the fundamental issues of power distribution as well as deals with the functioning of the electricity system in Czech republic. In this thesis there are also calculated two sample examples of two parallel cooperated units. In the first example, the optimized electric power is not outside of the control range but in the second, the optimized electric power is outside of the range. So there are two types of the calculations. As a part of the thesis there was made a mathematical model. The mathematical model based on the specified demand load in the network optimizes the eclectic power of three cooperating parallel units. This should lead to the fact that the operating costs will be minimized. In the model there is also a complete calculation of specific consumption and thermal efficiency. The reader of the thesis is able to do these calculations in five possible options.
Power Plant Units Cooperation - Optimization of Operating Parameters
Keywords: tepelná elektrárna; spolupráce elektrárenských bloků; tepelná účinnost; zvyšování tepelné účinnosti; regenerační ohřev; přihřívání páry; paralelní chod; matematický model; elektrárenský blok; thermal power plant; power plant units cooperation; thermal efficiency; increasing of the thermal efficiency; feedwater heater; reheating steam; parallel operation; mathematical model; power plant unit